LARVAL ANISAKID NEMATODES OF THE FLOUNDER, PARALICHTHYS ISOSCELES JORDAN, 1890 (PISCES: TELEOSTEI) FROM BRAZIL - Nunes Felizardo, Nilza (2009)
Between October 2006 and March 2008, 60 specimens of Paralichthys isosceles were captured in the littoral of the State of Rio de Janeiro, Brazil, to be investigated for anisakid nematodes, due to their zoonotic relevance. Five species of larval anisakid were present, in a total amount of 1,900 worms. One thousand eighty hundred and twenty larvae of Hysterothylacium sp., 71 of Raphidascaris sp., four of Terranova sp., three of Anisakis simplex and two of Contracaecum sp. were recovered. Parasites were found infecting the abdominal cavity, mesentery, intestine, liver, stomach mucosa, stomach, ovaries, abdominal musculature, and serosas of the heart, spleen, stomach, kidneys and ovaries. Hysterothylacium sp. appeared with a prevalence (P) of 100%, mean intensity (MI) of 30.3, range of infection (RI) of 1 to 596 and mean abundance (MA) of 30.3; Raphidascaris sp. with P = 36.7%, MI = 3.2, RI = 1 to 29 and MA = 1.18; Anisakis simplex with P = 5%, intensity (I) = 1 and MA = 0.05; Terranova sp. with P = 5%, MI = 1.3, RI = 1 to 2 and MA = 0.07; Contracaecum sp. with P = 3.3% I = 1 and MA = 0.03. This is the first report of parasitological indexes and sites of infection related to larval A. simplex, Contracaecum sp., Terranova sp., Hysterothylacium sp. and Raphidascaris sp. in Paralichthys isosceles. Larvae are described and illustrated. Paralichthys isosceles is a new host record for larvae of Anisakis simplex and Hysterothylacium sp.